PEMBELAJARAN SASTRA ERA VUCA - Nugraha, Dipa; Prayitno , Harun Joko; Suyitno; Sabardila, Atiqa; Huda , Miftakhul (JURNAL SKRIPTA, 2025)
Literary learning is important and cannot be underestimated. However, literature learning in Indonesia faces several problems, such as limited time in class, lack of resources, infrastructure and facilities, as well as teachers' competence and interest in literature. The situation has not improved. When the government published a national guidebook for learning and teaching literature entitled Panduan Penggunaan Rekomendasi Buku Sastra (Guide to Using Recommended Literary Books), sharp criticism emerged. Not to mention potential new problems that may arise in literature learning in the VUCA era. This article is a literature review article. Not only does it present a list of books and articles from library research that can be used as references and provide solutions to problems in learning literature, this article also discusses the urgency of learning literature, the objectives of learning literature, the position of teachers in learning literature, criteria for selecting literary works in learning, as well as designing literature learning in the VUCA era. This discussion ultimately leads to the conclusion that literature learning policies need to be carried out seriously and carefully because they have a big impact on the nation's future generations.